Study on suppression of otoacoustic emissions: lateral domain - Massola de Oliveira, Jerusa Roberta (2011)
A pon stimulation by contralateral, ipsilateral or bilateral noise, the medial olivocochlear efferent tract changes the amplitude of otoacoustic emissions relative to the tested ear, reducing or removing it; this resulted in a reduction/suppression effect of otoacoustic emissions. Differences in patterns of elimination/reduction of otoacoustic emissions between ears have been documented worldwide; there are, however, no Brazilian studies investigating the effect of lateral dominance.Aims: To compare the effect of the presence of deletion/reduction of otoacoustic emissions and their amplitude relative to lateral dominance in normal hearing adults.Methods: A clinical and experimental study. The sample comprised 75 individuals. The methodology was conventional - linear click intensity of 60 dB SPL; white noise was contralateral stimulation at 60 dB SPL.Description of results: There were no statistically significant differences between right and left ear results, in terms of asymmetry of the degree of otoacoustic emissions and the presence of suppression/reduction.Conclusion: There is no lateral dominance in the degree of otoacoustic emissions in the presence of suppression/reduction in the study population.